Rapid development of a tophus following ipsilateral hemiparesis. Issue 4 (April 1993) - Donegan, C F; Berman, P; Doherty, M
Abstract : An 85 year old man with a longstanding history of non-tophaceous gout developed a single large tophus, unassociated with inflammation, on his paretic leg over a six week period following an acute hemiplegia. The rapidity of tophus formation, its localisation to the paretic limb, and the apparent blunting of the acute inflammatory response represent a previously unreported interaction between gout and neurological deficit.